Assessing local health needs in primary care: understanding and experience in three English districts. Issue 2 (June 1998) - Jordan, J; Wright, J; Wilkinson, J; Williams, R
Abstract : BACKGROUND: Assessing the health needs of a local population has been promoted as a key component in effective targeting of healthcare services and quality improvement. The understanding and experience of assessing health needs in general practice were investigated in three English districts. AIM: To identify the issues surrounding the potential for assessing health needs in primary care. METHOD: Postal survey of 347 general practices in three health authorities. Telephone interviews with a random stratified sample of 35 general practitioners. RESULTS: Although most practices identified assessing health needs as important, it is clear that this identification was typically based on an understanding of assessing needs as primarily focused on individual patient care, based on clinical priorities and involving practice held data. Most practices had not undertaken local consultation, whatever their understanding of assessing health needs. The few practices which had completed population oriented, proactive assessment of needs considered it to have led to tangible improvements in clinical or practice management. Overall, there was apparent confusion over the nature and purpose of assessing needs, although the principled aims and objectives of a population oriented, proactive component to primary care were generally upheld. The need for additional resources and support was identified. In four out of the five cases where specifically population based assessment of health needs had been undertaken, the local public health department had been involved. CONCLUSION: The value of the concept of assessing health needs in primary care holds considerable uncertainty and ambivalence. The findings from this study show that any attempts to promote assessing needs into primary care which focus either primarily or exclusively on the provision of "education" are unduly simplistic. More fundamental questions about the perceived relevance and opportunities for assessing health needs should be considered if primary care groups are to meet future commissioning challenges.